Learning curve of transanal minimally invasive surgery for rectal neoplasm - Li, Xingwang; Guo, Shaoqing; Yao, Kunhou; Ge, Zheng; Li, Yuewei; Hu, Junhong; Xia, Hongping (Frontiers in Oncology, 2025)
ObjectivesThe field of view through transanal endoscopic provides new treatment approaches for solving complex clinical problems. TAMIS belongs to single-port endoscopic surgery, and the operation is complex. Analyzing the learning curve of TAMIS aims to facilitate its better clinical promotion.MethodsA retrospective cohort study analyzed the clinical data of 58 patients who underwent TAMIS by the same surgeon from January 2018 to October 2024. The learning curve of TAMIS was obtained using the cumulative sum (CUSUM) analysis, and the optimal number of surgeries was determined based on the peak value of the curve, Clinical indicators such as operative time, intraoperative blood loss, positive rate of circumferential margin, length of postoperative hospital stay, and incidence of postoperative complications were compared at different stages.ResultsAll 58 patients successfully underwent TAMIS. The optimum curve equation was y=0.016x3-2.0556x2+67.240x-150.103, R2 = 0.950, P<0.05. According to the peak value of the curve, 22 cases were determined as the minimum cumulative required cases for surgeons to cross the TAMIS learning curve. 58 cases were divided into two groups: the learning improvement group (Pre-proficiency) of the first 22 cases, and the proficiency group (Post-proficiency) of the latter 36 cases. Compared with Pre-proficiency stage, the Post-proficiency stage had shorter surgery duration, less intraoperative blood loss, and shorter length of postoperative hospital stay (P<0.05). There was no statistically significant difference in the observation indicators including positive rate of circumferential margin and incidence of postoperative complications between the two groups (P>0.05).ConclusionsThe learning curve of TAMIS can be divided into Pre-proficiency stage and Post-proficiency stage. 22 surgeries may be the number of surgeries required to cross the TAMIS learning curve.